(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Inflation, a continual increase in the price level, affects individuals, businesses, and government. Inflation is generally regarded as an important problem to be solved and has often been a primary concern of politicians and policy makers. To solve the inflation problem, we need to know something about its causes. The hypothesis adopted in this study states that inflation in Iraq causes by structural, monetary and financial disequilibrium In addition to the disequilibrium of the structure of foreign trade and the structure of output and employment. All these reasons contribute in feeding inflation. The unclear economic policies and their contradictions which are taken by successive governments have a significant influence in deepening the inflationary pressures. Moreover, the foreign factors played an essential role in aggravation inflation rates in Iraqi economy.